TINDAK TUTUR JURU PARKIR DI PASAR BALAI TANGAH KECAMATAN LINTAU BUO UTARA KABUPATEN TANAH DATAR - Windi Indra Lesmana; Novia Juita; Zulfadhli Zulfadhli (Faculty of Languages and Arts, Universitas Negeri Padang, 2013)
The purpose of this study was to describe the shape, strategies and function of speech acts parking attendants in Balai Tangah Market’s Sub-District Lintau Buo Utara on Tanah Datar District. The data of this study is speech acts parking attendants. Sources of data in this study is spoken language parking attendants. Data were collected by using scrutunize, tapping, note, observation, and interview. The results of the study are (1) forms of speech act parking attendants is directive, expressive, and representative, and (2) Strategies of speech acts parking attendants is speak overt without courtesy, speak overt with preamble positive politeness, and speak overt with preamble negative politeness, and (3) the function of speech act sparking attendants is competitive functionality, cooperating and conflicting.